Analysis of the Learning of Targhib wa Tarhib in Improving Students’ Understanding and Enthusiasm in Fiqh Muamalah at Al-Manshur Islamic Boarding School for Girls, Popongan, Klaten - Hanifa, Isma Nur; Salsabila, Rizquna; Ma'shum, Qodim (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the extent of the effect of integrating motivational elements in the teaching of Islamic jurisprudence (fiqh) on muamalah using the Targhib Wa Tarhib book, as well as to measure the students' understanding and enthusiasm in the learning process. The method used is qualitative by conducting participatory observation, interviews, and documentation collection. This research was conducted at the Al-Manshur Popongan West Complex Girls' Islamic Boarding School, Klaten, with research subjects consisting of kyai, boarding school administrators, and students. The findings of the study indicate that teaching based on the Targhib Wa Tarhib book is effective in improving students' understanding of muamalah material, which is characterized by the students' ability to connect the concepts taught with everyday life and changes in behavior towards a more positive direction. Furthermore, students show very high enthusiasm for learning, seen from their desire to participate in activities, actively ask questions, and take part in discussions both inside and outside the classroom environment. Even though Targhib Wa Tarhib does not discuss muamalah in a technical way, the motivational values contained in it have the potential to shape the moral and spiritual awareness of students in interacting within muamalah. Thus, integrating motivational elements in the learning process has been proven to be able to create meaningful learning experiences, not only in the cognitive realm but also in effective and social aspects.